Interaction network of the ribosome assembly machinery from a eukaryotic thermophile - Baßler, Jochen; Ahmed, Yasar Luqman; Kallas, Martina; Kornprobst, Markus; Calviño, Fabiola R.; Gnädig, Marén; Thoms, Matthias; Stier, Gunter; Ismail, Sherif; Kharde, Satyavati; Castillo, Nestor; Griesel, Sabine; et al. (Protein science, 2017)
Ribosome biogenesis in eukaryotic cells is a highly dynamic and complex process innately linked to cell proliferation. The assembly of ribosomes is driven by a myriad of biogenesis factors that shape pre-ribosomal particles by processing and folding the ribosomal RNA and incorporating ribosomal proteins. Biochemical approaches allowed the isolation and characterization of pre-ribosomal particles from Saccharomyces cerevisiae, which lead to a spatiotemporal map of biogenesis intermediates along the path from the nucleolus to the cytoplasm. Here, we cloned almost the entire set (∼180) of ribosome biogenesis factors from the thermophilic fungus Chaetomium thermophilum in order to perform an in-depth analysis of their protein-protein interaction network as well as exploring the suitability of these thermostable proteins for structural studies. First, we performed a systematic screen, testing about 80 factors for crystallization and structure determination. Next, we performed a yeast 2-hybrid analysis and tested about 32,000 binary combinations, which identified more than 1000 protein-protein contacts between the thermophilic ribosome assembly factors. To exemplary verify several of these interactions, we performed biochemical reconstitution with the focus on the interaction network between 90S pre-ribosome factors forming the ctUTP-A and ctUTP-B modules, and the Brix-domain containing assembly factors of the pre-60S subunit. Our work provides a rich resource for biochemical reconstitution and structural analyses of the conserved ribosome assembly machinery from a eukaryotic thermophile.